A Fully Integrated Architecture for Fast and Accurate Programming of Floating Gates Over Six Decades of Current - Basu, Arindam; Hasler, Paul E (IEEE transactions on very large scale integration (VLSI) systems, 2011)
This paper presents an on-chip system with digital serial peripheral interface (SPI) interface that enables accurate programming of floating gate arrays at a high speed. The main component allowing this speedup is a floating point current measuring analog-to-digital convertor (ADC). The ADC comprises a wide range logarithmic transimpedance amplifier (TIA) followed by a linear ramp ADC. The TIA operates over seven decades of current going down to sub-pA levels. It incorporates an adaptive biasing scheme to save power. The topology provides a relatively temperature independent measurement of the floating-gate voltage. The TIA-ADC combination operates over six decades at a thermal noise limited accuracy of 9.5 bits when average conversion time is around 500 μs. The system features level-shifters and selection circuitry at the periphery of the floating gate array, current-steering digital-to-analog converters (DACs) to set gate and drain voltages, and SPI for a microprocessor or field-programmable gate array (FPGA). Algorithms using either pulse-width modulation or drain voltage modulation can be implemented on this platform. We present data for this system from 0.5 μm AMI and 0.35 μ m TSMC processes.